COMMUNITY STRUCTURE OF MACROZOOBENTHOS AS BIOINDICATOR OF WATER QUALITY IN THE OGAN RIVER AROUND BATURAJA CITY - Siti Aulia Nurainah; Zazili Hanafiah (BIOVALENTIA: Biological Research Journal, 2022)
Macrozoobenthos has an important role in the waters. The river is one example of a water body where macrozoobenthos can be used as an indicator of water pollution. This study aims to calculate the community structure of macrozoobenthos and the water quality in the Ogan River around Baturaja City. Sampling was carried out by purposive sampling method in 5 stations, in which each station had 5 sampling points determined based on differences in microhabitat, namely stonny, gravel, sandy, and litter conditions around the edge of vegetation. The results revealed that macrozoobenthos found in the Ogan River consisted of 6 classes (i.e., Bivalvia, Crustacea, Gastropods, Insecta, Oligochaeta, and Turbellaria), 12 orders, 21 families, and 30 genera. The density of macrozoobenthos species ranged from 598 to 1367 ind/m2. The diversity index value in the Ogan River around Baturaja City ranged from 1.117 to 2.22 with a moderate category. In addition, the community similarity index of the five stations reached ≥ 50%, except for stations III and V (44%). Seemingly that the macrozoobenthos community in the waters of the Ogan River around Baturaja City was relatively the same. Therefore, the community structure of the Ogan River around Baturaja City was relatively stable.